Tălmăcitori în „Graiul Nou” - Carmen Brăgaru (Revista de Istorie și Teorie Literară)
The present study aims to describe as thoroughly as possible an important propagandistic newspaper, today obscure, significantly entitled The New Voice (or The New Language) which was issued in Romania by the Red Army Political Direction between 1944 and 1948. The subjective (read: not objective) information used to influence or tame the Romanian audience was signed by important Russian writers of the period who played an essential part not only in the literary field but also in the manipulative approach of the social, historical and political aspects. Their texts as well as the poems, songs or folklore pieces carefully selected from different areas of the Soviet Bloc needed gifted Romanian translators dedicated to the communist cause. Most of them were young, of the Bessarabian or Jewish origins, knowing the Russian language more or less, and they were sincerely involved in the russification process which had just begun on the Romanian territory. What they translated draws the map of the active propaganda in the middle forties of the last century, but each one’s temperament and talent is shown by how they translated.